STRATEGI KOMUNIKASI INTERPERSONAL KEPALA DESA DALAM UPAYA PENCEGAHAN COVID-19 DI DESA KALIAMAN KECAMATAN KEMBANG KABUPATEN JEPARA - Murniati Murniati; Muqodim Muqodim (An-Nida : Jurnal Komunikasi Islam, 2021)
This research is motivated by the increasingly widespread spread of the Covid-19 virus, resulting in restrictions on interacting. Based on these problems, the Kaliaman Village Head took follow-up actions in preventing Covid-19 through interpersonal communication strategies. Interestingly, in this case, what interpersonal communication strategy does the Village Head do to the community. Therefore, it is appropriate to conduct a research entitled "Interpersonal Communicatidon Strategy of the Village Head to the Community in Efforts to Prevent Covid-19 in Kaliaman Village." This study aims to 1. To find out the interpersonal communication strategy of the Village Head to the community in an effort to prevent Covid-19 in Kaliaman Village, Kembang District, Jepara Regency. 2. To find out the supporting and inhibiting factors of the Village Head's interpersonal communication strategy to the community in an effort to prevent Covid-19 in Kaliaman Village. This type of research is a qualitative research with descriptive method. This data was obtained from interviews, observations and documentation. The results show that 1. The Head of Kaliaman Village, Kembang District, Jepara Regency in preventing Covid-19 dominates interpersonal communication which classifies them as Musren Bangdes (Village Planning and Development Deliberation), Downward Vertical Communication (Downward Communication), Cultural Communication (communication to residents) , Media socialization (banners and hand washing).2.The supporting factor for preventing Covid-19 in Kaliaman Village is the collaboration between the Kaliaman Village and the Jepara Regency government, the Village Task Force, Village Volunteers, and the Kaliaman Village apparatus, The inhibiting factor is that the inhibiting factor comes from the community itself